2019
DOI: 10.1021/acs.est.9b03956
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium Desorption from Nuclear Melt Glass-Derived Colloids and Implications for Migration at the Nevada National Security Site, USA

Abstract: The migration of low levels of plutonium has been observed at the Nevada National Security Site (NNSS) and attributed to colloids. To better understand the mechanism(s) of colloidfacilitated transport at this site, we performed flow cell desorption experiments with mineral colloid suspensions produced by hydrothermal alteration of NNSS nuclear melt glass, residual material left behind from nuclear testing. Three different colloid suspensions were used, 1) colloidal material from hydrothermal alteration of nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Pu contamination of soil and groundwater is a legacy of past activities associated with the production of nuclear weapons (e.g., Hanford Site and Savannah River Site, USA), nuclear weapon tests, as well as the discharge of radionuclides from commercial fuel reprocessing into the environment (e.g., Sellafield, UK). The fate and transport of Pu in water is governed by processes that include redox reactions, , adsorption to and desorption from mineral surfaces, dissolution and precipitation, interactions with natural organic matter (NOM), , and microbial activity which can mediate these geochemical processes and directly impact Pu behavior. Under environmental conditions, Pu can exist as Pu­(III), Pu­(IV), Pu­(V), and Pu­(VI) . Environmental redox processes play a critical role in controlling Pu mobility as the reduced forms (III/IV) are generally 2–3 orders of magnitude less mobile and have higher affinity for mineral surfaces and organic matter than the oxidized forms (V/VI) in most environments. ,, However, formation of intrinsic Pu­(IV) oxide/hydroxide and pseudo Pu colloids could facilitate the subsurface transport of Pu under certain conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pu contamination of soil and groundwater is a legacy of past activities associated with the production of nuclear weapons (e.g., Hanford Site and Savannah River Site, USA), nuclear weapon tests, as well as the discharge of radionuclides from commercial fuel reprocessing into the environment (e.g., Sellafield, UK). The fate and transport of Pu in water is governed by processes that include redox reactions, , adsorption to and desorption from mineral surfaces, dissolution and precipitation, interactions with natural organic matter (NOM), , and microbial activity which can mediate these geochemical processes and directly impact Pu behavior. Under environmental conditions, Pu can exist as Pu­(III), Pu­(IV), Pu­(V), and Pu­(VI) . Environmental redox processes play a critical role in controlling Pu mobility as the reduced forms (III/IV) are generally 2–3 orders of magnitude less mobile and have higher affinity for mineral surfaces and organic matter than the oxidized forms (V/VI) in most environments. ,, However, formation of intrinsic Pu­(IV) oxide/hydroxide and pseudo Pu colloids could facilitate the subsurface transport of Pu under certain conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Environmental redox processes play a critical role in controlling Pu mobility as the reduced forms (III/IV) are generally 2–3 orders of magnitude less mobile and have higher affinity for mineral surfaces and organic matter than the oxidized forms (V/VI) in most environments. ,, However, formation of intrinsic Pu­(IV) oxide/hydroxide and pseudo Pu colloids could facilitate the subsurface transport of Pu under certain conditions . The presence of these colloids further complicates the fate of Pu as it can lead to mobilization of the reduced forms of Pu via colloid-facilitated transport. ,, …”
Section: Introductionmentioning
confidence: 99%
“…15 Both the sorption/desorption of Pu to mineral colloid surfaces (pseudocolloids) and formation of Pu oxide colloids (intrinsic colloids) associated with mineral surfaces, as well as Pu coprecipitation with secondary minerals are all likely important environmental processes under a range of geochemical conditions. 11,14,22,57,58 For example, in groundwater at the Mayak site (Russia), colloidal amorphous iron oxides with associated Pu were found up to 4 km away from the contamination source. 59 In contaminated soils at Los Alamos National Laboratory, Batuk et al 60 identified unusual Pu−Fe particles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At high Pu concentrations (>10 –8 M), Pu­(IV) intrinsic colloids have been shown to form on the surface of various oxide minerals including iron oxy­(hydroxide) minerals. ,,, On the goethite surface, Pu­(IV) colloids may undergo a lattice distortion, because of epitaxial growth, which leads to a stronger surface binding compared to other mineral phases, such as quartz . Both the sorption/desorption of Pu to mineral colloid surfaces (pseudocolloids) and formation of Pu oxide colloids (intrinsic colloids) associated with mineral surfaces, as well as Pu coprecipitation with secondary minerals are all likely important environmental processes under a range of geochemical conditions. ,,,, For example, in groundwater at the Mayak site (Russia), colloidal amorphous iron oxides with associated Pu were found up to 4 km away from the contamination source . In contaminated soils at Los Alamos National Laboratory, Batuk et al .…”
Section: Introductionmentioning
confidence: 99%
“…The authors attempted to describe the subsequent leaching of plutonium from these colloids. The results suggest that the hydrothermal conditions during colloid formation affect the Pu desorption rates from the colloids (Joseph et al, 2019 ). The desorption rates of Pu from the colloids that were formed at 140°C can be modeled based on the kinetics of Pu sorption/desorption onto montmorillonite at room temperature.…”
Section: Plutoniummentioning
confidence: 99%